Optimalisasi Pembelajaran Literasi Numerasi Melalui Pelatihan Penggunaan Website Google Sites bagi Guru Komunitas Belajar - Nurul Renaningtias; Atika Susanti; Bagus Mirzana; Cahyo Prasetyo; Dwi Lestari (I-Com: Indonesian Community Journal, 2024)
The main goal of this community service activity is to enhance teachers' numeracy literacy skills through the use of Google Sites. The partner for this service activity is SDN 8 Bengkulu Tengah, Desa Rindu Hati. The method used for this community service includes the IPPE method, which comprises: (1) Needs Identification, (2) Planning, (3) Training Implementation, and (4) Evaluation. The evaluation instrument used was a test sheet. Based on the assessment results, there was a significant improvement in teachers' skills, with the average pretest score rising from 51.57 to 85.56 in the posttest. The N-Gain score averaged 0.74, which falls into the "High" category. This indicates that the community service activity successfully achieved its goal of improving teachers' ability to optimize numeracy literacy instruction through the use of Google Sites and providing a useful training module. It is recommended that teachers consistently apply the techniques and tools learned in the classroom and integrate these methods into the independent curriculum across all subjects.